1989
DOI: 10.1073/pnas.86.1.182
|View full text |Cite
|
Sign up to set email alerts
|

Cytolysis by tumor necrosis factor is preceded by a rapid and specific dissolution of microfilaments.

Abstract: Tumor necrosis factor (TNF) is cytotoxic to certain transformed cells, whereas normal cells are resistant to its effects. The resistance of normal cells can often be overcome by treatment with inhibitors of transcription or translation such as actinomycin D or cycloheximide (CHI), suggesting that normal cells produce a protein(s) that protects them from TNF-induced cytolysis. In this report, we examine the mechanism of cytolysis in a 3T3-like mouse cell line, C3HA, which was sensitized to TNF by treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 24 publications
4
22
0
Order By: Relevance
“…Later on, and more particularly subsequent to cell death, this specificity was lost. We have no experimental data to explain the inolccular basis of the latter phenomenon, but it has been shown that TNF, albeit at very high concentrations, increases the permeability of liposomes [54], and that TNF-induced loss of cell viability is accompanied by lysis of the plasma membrane [55]. Furthermore, it is known that PL activity is affected by structural perturbations of the cell membrane [56].…”
Section: Discussionmentioning
confidence: 93%
“…Later on, and more particularly subsequent to cell death, this specificity was lost. We have no experimental data to explain the inolccular basis of the latter phenomenon, but it has been shown that TNF, albeit at very high concentrations, increases the permeability of liposomes [54], and that TNF-induced loss of cell viability is accompanied by lysis of the plasma membrane [55]. Furthermore, it is known that PL activity is affected by structural perturbations of the cell membrane [56].…”
Section: Discussionmentioning
confidence: 93%
“…Cytochalasin D treatment abolished the protective effect of PKB/Akt, placing actin polymerization downstream of PI3K and PKB/Akt in cell survival. TNFinduced death by cycloheximide has been associated with the disruption of the actin cytoskeleton (Scanlon et al, 1989), and recent reports implicate changes in the dynamics of the actin cytoskeleton to mitochondrial changes in cell death (Gourlay and Ayscough, 2005). Mitochondria are key to the execution of apoptosis and PKB/Akt controls the expression or translocation of antiapoptotic proteins (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of TNF signalling on the actin cytoskeleton were initially discovered in the context of cell death (Scanlon et al, 1989). Among the most apparent results of TNF-induced apoptosis are drastic changes in cell morphology -such as the rounding-up of the cell and blebbing of the plasma membrane -and the concomitant reorganization of the cytoskeleton.…”
Section: Tnfα Signals To the Actin Cytoskeletonmentioning
confidence: 99%
“…In addition, some effects of TNF signalling that have been primarily defined in pro-apoptotic signalling may rather be part of the inflammatory repertoire. Several pro-inflammatory changes that are associated with TNFα treatment [such as increased pulmonary or vascular endothelial-cell permeability (Kohno et al, 1993;Koss et al, 2006;WojciakStothard et al, 1998), and neutrophil or fibroblast recruitment to sites of inflammation (Lokuta and Huttenlocher, 2005;Postlethwaite and Seyer, 1990)] and pro-apoptotic effects associated with TNFα treatment [such as osteoblast apoptosis, fibroblast cytolysis or epithelial-cell apoptosis (Domnina et al, 2002;Domnina et al, 2004;Scanlon et al, 1989;Triplett and Pavalko, 2006)] all involve effects on the cytoskeleton and the cellular machinery regulating the cytoskeleton. The pro-inflammatory effects of TNFα treatment on cultured cells and the associated effects on the cytoskeleton are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%